Efektivitas E-Modul Berbasis Kearifan Lokal kota Palembang Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Sma pada Materi Fluida Statis - Yeni Utami; Ketang Wiyono; Syuhendri (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the effect of implementing an e-module based on local wisdom in the city of Palembang on static fluid material on the critical thinking skills of high school students. This type of research is a quasi-experiment using the pretest-posttest method. The population of this study was class XI students of SMA Negeri 2 Palembang City. Data analysis techniques use quantitative data to analyze data collected from student achievement scores. The results of the pretest data analysis on critical thinking skills averaged 53, while the average post-test score was 82. This shows that students' critical thinking skills have improved after using the static fluid e-module based on local wisdom in Palembang. This is proven by the results of the N-gain test analysis showing that students with critical thinking skills scored 0.60 in the medium category.